The effects of integration of New Zealand's Roman Catholic schools : a thesis submitted in fulfilment of the requirement for the degree of Master of Arts in Sociology at Massey University - Atkins, E. Anne (Massey University, 1984)
The principle aim of this thesis was to investigate Integration, in particular the integration of Roman Catholic Schools in New Zealand. By March 1983 every Roman Catholic School had integrated (258).1 Historically, in the 1960's and early 1970's, 252 teaching Religious left their schools, many left religious life. Their defection created a spiritual problem, disillusioned youth left the Church. At this point, the Catholic Authorities missed an opportunity: to investigate causes of the spiritual malaise and to ask serious questions about whether Catholic schools were the best solution to it. Instead they turned a spiritual problem into a financial one by replacing the religious with paid lay staff. In turn, this financial problem became a political one, with the Catholic Authorities seeking increased Government assistance to their schools. In 1973, the Labour Party, in Government, called a State Aid Conference from which a Steering Committee drafted the concept of Integration, in 1975, to become a Bill (Act?). This controversial Private Schools Conditional Integration Act, termed the 'shotgun wedding', steamrolled through the dying session of Parliament amidst continual protest from the National Party, in Opposition. The Act provided for the conditional and voluntary integration of private schools into the State system on a basis in which their special character is pre-served and safeguarded. Special character is the Trojan Horse inserted into a Bill that has had the effect of jeopardising the goodwill hard won by many Catholics in New Zealand regarding their schools. With Integration, the Roman Catholic Bishops agreed to meet the upgrading costs of all New Zealand Catholic Schools before the State is prepared to take over their future maintenance. Few non-Catholic Private Schools went ahead with this upgrading integration condition having got what they wanted: a continuance of State Aid. This serious financial commitment signed for all Roman Catholic schools has caused a financial crisis within the Catholic Church diverting money and energy from other Church projects and neglecting Catholic children in State schools. Besides the enormous cost to the Catholic Church, millions of dollars of Housing Corporation money is loaned to Roman Catholic schools for two-thirds2 of their cost at a time of loan cut-backs. Whilst State schools are drastically cut back financially there appears to be no cut back financially of Government money to integrated schools. Bitterness and ill-feeling is mounting in the State sector. What a cost to the Catholic Church for it seems their spiritual problem that became a financial problem, then a political one is boomeranging back as a spiritual problem. A questionnaire on Faith (taken from the Baptismal questions) and on practice (from Canon Law) was given, as part of this thesis, to Catholic children in State schools and in Roman Catholic schools, under exactly the same conditions [State school Catholics score higher in Faith]. Was it worth it to pour millions of dollars into a system, from which 600 religious had left since Integration, and which still claims to have a special character belonging to the Roman Catholic church, with half its lay-staff non-Catholics?
Keywords: Education state; New Zealand Education; Catholic Church